Ground temperature changes on the Kaffiøyra Plain (Spitsbergen) in the summer seasons, 1975–2014 - Araźny Andrzej; Przybylak Rajmund; Kejna Marek (Polish Polar Research, 2016)
This paper provides an overview of the results of research on changes in ground temperature down to 50 cm depth, on the Kaffiøyra Plain, Spitsbergen in the summer seasons. To achieve this, measurement data were analysed from three different ecotopes (CALM Site P2A, P2B and P2C) – a beach, a moraine and tundra – collected during 22 polar expeditions between 1975 and 2014. To ensure comparability, data sets for the common period from 21 July to 31 August (referred to as the “summer season” further in the text) were analysed. The greatest influence on temperature across the investigated ground layers comes from air temperature (correlation coefficients ranging from 0.61 to 0.84). For the purpose of the analysis of the changes in ground temperature in the years 1975–2014, missing data for certain summer seasons were reconstructed on the basis of similar data from a meteorological station at Ny-Ålesund. The ground temperature at the Beach site demonstrated a statistically-significant growing trend: at depths from 1 to 10 cm the temperature increased by 0.27–0.28°C per decade, and from 20 to 50 cm by as much as 0.30°C per decade. On the Kaffiøyra Plain, the North Atlantic Oscillation (NAO) has a greater influence on the ground and air temperature than the Arctic Oscillation (AO).